Review of Shadow Archives: The Lifecycles of African American Literature - Abdullah, Hogar Najm (AMERICANA E-journal of American Studies in Hungary, 2021)
Shadow Archives: The Lifecycles of African American Literature Jean-Christophe Cloutier New York: Columbia University Press, 2019 383 pages ISBN: 978-0231193313